Medicinal potential of Melodorum gracile and Mkilua fragrans extracts - Sylvester Leonard Lyantagaye (Journal of Applied Pharmaceutical Science, 2014)
Crude ethanol extracts of Melodorum gracile and Mkilua fragrans were screened for antimicrobial activity against Streptococcus agalactiae, Staphylococcus aureus, Salmonella gallinarum and Escherichia coli of veterinary importance. Agar diffusion technique was used to determine the inhibition of microbial growth and broth dilution technique was used to determine MIC and MBC. The crude extracts exhibited predominantly antibacterial activity with the root extract showing the strongest inhibition against the test bacteria at a MIC of between 7 µg/ml and 500 µg/ml. The study has shown that Mkilua fragrans extract is very potent against Streptococcus agalactiae and Staphylococcus aureus but no effect against Salmonella gallinarum and Escherichia coli. The study also showed that Melodonium gracile extracts were potent against Streptococcus agalactiae, Staphylococcus aureus, Salmonella gallinarum and Escherichia coli. Most of the plant extracts were significantly lethal towards brine shrimps. This is the first scientific evaluation of the veterinary medicinal potential of the Melodorum gracile and Mkilua fragrans indigenous to Tanzania, providing the baseline for further investigations on the plants towards new drug discovery.
Keywords: Antimicrobial activity,Melodorum gracile,Mkilua fragrans,Tanzania,veterinary.